Co-administration of Anti microRNA-124 and -137 Oligonucleotides Prevents Hippocampal Neural Stem Cell Loss Upon Non-convulsive Seizures - Bielefeld, Pascal; Schouten, Marijn; Meijer, Guido M.; Breuk, Marit J.; Geijtenbeek, Karlijne; Karayel, Sedef; Tiaglik, Alisa; Vuuregge, Anna H.; Willems, Ruth A.L.; Witkamp, Diede; Lucassen, Paul J.; Encinas, Juan M.; et al. (Frontiers in Molecular Neuroscience, 2019)
Convulsive seizures promote adult hippocampal neurogenesis (AHN) through a transient activation of neural stem/progenitor cells (NSPCs) in the subgranular zone (SGZ) of the dentate gyrus. However, in a significant population of epilepsy patients, non-convulsive seizures are observed. The response of NSPCs to non-convulsive seizure induction has not been characterized before. We here studied first the short-term effects of controlled seizure induction on NSPCs fate and identity. We induced seizures of controlled intensity by intrahippocampally injecting increasing doses of the chemoconvulsant kainic acid (KA) and analyzed their effect on subdural EEG recordings, hippocampal structure, NSPC proliferation and the number and location of immature neurons shortly after seizure onset. After establishing a KA dose that elicits non-convulsive seizures (ncSZ), we then analyzed the effects of ncsZ on NSPC proliferation and NSC identity in the hippocampus. ncSZ specifically triggered neuroblast proliferation, but did not induce proliferation of NSPCs in the SGZ, 3 days post seizure onset. However, non-convulsive seizures induced significant changes in NSPC composition in the hippocampus, including the generation of reactive NSCs. Interestingly, intrahippocampal injection of a combination of 2 anti microRNA oligonucleotides targeting microRNA-124 and -137 normalized neuroblast proliferation and prevented NSC loss in the dentate gyrus upon ncSZ. Our results show for the first time that non-convulsive seizures induce significant changes in neuroblast proliferation and NSC composition. Simultaneous antagonism of both microRNA-124 and -137 rescued seizure-induced alterations in NSPC, supporting their coordinated action in the regulation of NSC fate and proliferation and their potential for future seizure therapies.